Mathematical proficiency for all students : toward a strategic research and development program in mathematics education - Ball, Deborah Loewenberg, 1954- (RAND, 2003)
This report grew out of concerns about the weak levels of mathematical proficiency among U.S. citizens and the inequities in the achievement of students of different ethnic, cultural, and social groups. Debates concerning the value of specific curricula, requirements for teacher knowledge, and standards that students should meet are poorly informed because research evidence is lacking. The report proposes a long-term, strategic program of research and development in mathematics education with the twin goals of raising the level of mathematical proficiency and removing inequalities. The program addresses issues directly related to teaching and learning by focusing on three domains: developing teachers' mathematical knowledge for teaching; teaching and learning mathematical practices--the mathematical know-how that characterizes expertise in learning and using mathematics; and teaching and learning algebra in grades K-12. To gain the necessary political support for the program, the report recommends that work begin in three key areas: studies providing evidence for necessarily political decisions concerning standards of mathematical proficiency to be met by students; studies of current instructional practice and curriculum in U.S. classrooms; and studies that assemble existing measures of mathematical performance or develop new ones that can be used in the proposed program.